2012
DOI: 10.1038/oby.2011.140
|View full text |Cite
|
Sign up to set email alerts
|

Male Inclusion in Randomized Controlled Trials of Lifestyle Weight Loss Interventions

Abstract: The prevalence of obesity is similar for men (32.2%) and women (35.5%). It has been assumed that lifestyle weight loss interventions have been developed and tested in predominately female samples, but this has not been systematically investigated. The aim of this review was to investigate total and ethnic male inclusion in randomized controlled trials of lifestyle interventions. PUBMED, MEDLINE, and PSYCHINFO were searched for randomized controlled trials of lifestyle weight loss interventions (N = 244 studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
345
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(364 citation statements)
references
References 15 publications
17
345
1
1
Order By: Relevance
“…Our data confirm those of Pagoto and colleagues' systematic review [4]; that men are less likely to take part in RCTs, and comprised 27% of all participants in their RCTs, compared with 37% in the studies providing data here. The Pagoto and colleagues' review did not focus on recruitment by sex in the same trial.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data confirm those of Pagoto and colleagues' systematic review [4]; that men are less likely to take part in RCTs, and comprised 27% of all participants in their RCTs, compared with 37% in the studies providing data here. The Pagoto and colleagues' review did not focus on recruitment by sex in the same trial.…”
Section: Discussionsupporting
confidence: 90%
“…In a systematic review, Pagoto and colleagues [4] found that only 27% of participants in randomised trials were men, although the percentage was higher in interventions for obesity with related comorbidities (36% men). There was also a trend towards lower participation by men in group-based interventions (24%), compared with individual counselling (29%) or mail/e-mail/internet (34%); however, the male/female mix of the group-based interventions was not specified.…”
Section: Introductionmentioning
confidence: 99%
“…The serving of a smaller portion of a complete meal may increase the likelihood of balanced intake than would eating patient-selected parts of a larger meal. Moreover, the recommended dietary intake is lower for women than for men, and women might be more concerned about their weight as has been reflected by the underrepresentation of men in clinical weight-loss trials (27). We are aware that sex also stands as a proxy for other patient characteristics such as weight, height, and body composition.…”
Section: Discussionmentioning
confidence: 99%
“…Men are also underrepresented in obesity and weight loss research. Two systematic reviews that examined studies published between 1997-2004 and 1999-2009 found that only 27% of participants were male (Franz, VanWormer, & Crain, 2007;Pagoto, Schneider, Oleski, Luciani, Bodenlos, & Whited, 2011). Furthermore, only three of the 80 studies had male-only groups as opposed to 19 studies which had female-only groups.…”
Section: Men and Weight Management Programsmentioning
confidence: 99%